Biotech Innovations and Fundamental Rights - Bin, Roberto; Lorenzon, Sara.; Lucchi, Nicola; SpringerLink (Online service) (Milano : Springer Milan, 2012)
Biotechnology is a recognized research area that has increasingly advanced into new technologies and modern practices raising several legal, ethical and regulatory issues. The revolutionary speed of biotech innovations has had a significant impact on the protection of the rights of the individual. Fundamental rights provide a framework within which the justification of limitations and restrictions to biotechnology innovations and research results have to be assessed. The legal regulation of scientific research and scientific investigations impact more and more directly on the freedom of research and therapies as well as on the broad diffusion of knowledge. Closely related is also the debated question of the technological manipulation of life and the boundary of scientific knowledge with regard to the topical question of genetic invention patents and their side effects on access to scientific information and health care opportunities. Drawing on expertise from different disciplines, the volume comprises invited papers and plenary presentations given at the conference entitled (3z(BBiotech Innovations & Fundamental Rights(3y (Bthat took place on Januray 20-21 2011 at the Department of Juridical Sciences of the University of Ferrara. Each contribution covers a different aspect of the legal and scientific issues involved in regulation of biotechnology. In particular the focus of attention has been given to genetic research, genetic data, freedom of scientific research in genetics and biotech patents.s
Keywords: Law; Human genetics; Biochemistry; Constitutional law; Law; Constitutional Law; Human Genetics; Biochemistry, general